Prospects of Taiwan's solar energy development and policy formulation - Shan-Shan Kung; Hailing Li; Chih-Chun Kung (Heliyon, 2024)
Taiwan lacks energy stock and has been paying great attention to developing renewable energy to improve energy security and sustain economic growth. Solar energy is attractive to Taiwan's government as the recorded radiation is substantial, and a significant amount of fallow land is available for panel installation. This study investigates the potential solar energy production from Crystalline silicon (c-Si) and cadmium Telluride thin-film (CdTe) cell systems, estimates each system's capital requirement, and compares the economic and environmental benefits to explore effective investment strategy. The results show that, on average, the c-Si module could produce 10,644 GWh per year while the CdTe mode would yield a total electricity of about 9365 GWh. The useful life also plays an essential role in the investment requirement. With a 30-year useful life, the systems can reduce the annualized installation and maintenance cost to about NT$3.16 billion. In terms of offset efficiency, every MWh produced would result in at least 13.63–15.49 metric ton of carbon emission offset, and the offset value per GWh can be up to NT$5.77 million, which provide attractive economic incentives to energy suppliers. We point out that the acquisition of low-cost financing sources such as green bonds, as well as the improvement of current emission trading systems (ETS), would greatly benefit solar energy development.